Development and characterization of Ti-6Al-4V to 304L stainless steel gradient components fabricated with laser deposition additive manufacturing. (15th August 2016) - Reichardt, Ashley; Dillon, R. Peter; Borgonia, John Paul; Shapiro, Andrew A.; McEnerney, Bryan W.; Momose, Tatsuki; Hosemann, Peter
Abstract: In this study, a multi-hopper laser deposition system is used to additively manufacture functionally graded Ti-6Al-4V to 304L stainless steel components with a vanadium interlayer. Grain morphology, phase, and composition are mapped along the component gradients with electron backscatter diffraction (EBSD) and energy dispersive X-ray spectroscopy (EDS), and mechanical property changes are assessed utilizing Vickers hardness and nanoindentation. Precipitation of brittle intermetallic compounds such as FeTi and the formation of an Fe-V-Cr sigma phase are confirmed to be the causes of mid-fabrication cracking in the components. Guided by multicomponent phase diagrams, alternate paths in composition space are proposed to strategically avoid unfavorable phase formation along the gradient. Composition-dependent adjustment of process parameters is also proposed to reduce the prevalence of observed powder inclusions, homogenize grain morphology, and improve component mechanical properties. Graphical abstract: Highlights: Gradient components transitioning from Ti-6Al-4V to stainless steel were fabricated using laser metal deposition. EBSD mapping of grain morphology and phase revealed the need for composition-dependent changes in process parameters. Thermodynamic modeling successfully predicted brittle phase formation and guided adjustment of the gradient path.